Trichosanthes Dioica Roxb.: An Overview - NITIN KUMAR (International Journal of Pharma and Bio Sciences, 2011)
Trichosanthes, a genus of family Cucurbitaceae is an annual or perennial herb distributed in tropical Asia and Australia. Pointed gourd (Trichosanthes dioica Roxb.) is known by a common name of parwal and cultivated mainly as a vegetable. Juice of leaves of T. dioica is used as tonic, febrifuge, in oedema, alopecia and in subacute cases of enlargement of liver. In Charaka Samhita leaves and fruits find mention for treating alcoholism and jaundice. A lot of pharmacological work has been scientifically carried out on various parts of T. dioica but some other traditionally important therapeutical uses are also remaining to proof till now scientifically. According to ayurveda leaves of the plant are used as antipyretic, diuretic, cardiotonic, laxative, antiulcer, etc. It is also used in skin disorder by some communities of Asia traditionally. The various chemical constituents present in T. dioica are vitamin A, vitamin C, tannins, saponins, tetra and pentacyclic triterpenes etc.